SKALA PRIORITAS PEMBANGUNAN EKONOMI PERTANIAN DI KABUPATEN BIAK NUMFOR PAPUA - SYAFRUDDIN DAERLAN (Universitas Sebelas Maret, 2010)
One of the success of agriculture development is planned. Pledge sector are capable sector to draw and pusc economic sector so that enter all economic sector can be agriculture pith economic growth, creating opportunity job, improving eamings and reducing poomess people.